2022
DOI: 10.3390/su14159724
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Barriers in Humanitarian Supply Chains for Cyclone in Coastal Areas of Bangladesh: An Interpretive Structural Modeling (ISM) Approach

Abstract: Bangladesh has frequently been affected by natural hazards, notably, cyclones in coastal areas. Humanitarian organizations are always active in helping affected communities through effective humanitarian supply-chain management by providing humanitarian goods and services, which is crucial to aiding vulnerable people after a natural catastrophe. However, some factors cause significant difficulties in achieving feasible humanitarian supply-chain (HSC) management that eventually ends up as a disfunctional and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…The five perspectives considered were managerial (P1), information (P2), integration (P3), production (P4), and environmental (P5). These perspectives were adopted by Tyagi et al [ 67 ], Sim et al [ 68 ] and Al Amin et al [ 69 ], who added the environmental perspective to enhance sustainability performance. The study used Kappa statistics to measure the consistency of each factor from five perspectives.…”
Section: Methodsmentioning
confidence: 99%
“…The five perspectives considered were managerial (P1), information (P2), integration (P3), production (P4), and environmental (P5). These perspectives were adopted by Tyagi et al [ 67 ], Sim et al [ 68 ] and Al Amin et al [ 69 ], who added the environmental perspective to enhance sustainability performance. The study used Kappa statistics to measure the consistency of each factor from five perspectives.…”
Section: Methodsmentioning
confidence: 99%
“…Singh et al (2018) identified and analyzed factors for developing resilience in humanitarian supply chains using the fuzzy MICMAC approach [56][57][58]. Rahman Md Mostafizur et al (2022) used Interpretive Structural Modeling (ISM) to assess the barriers in the humanitarian supply chain in coastal Bangladesh under the influence of cyclones [59]. Giedelmann-L Nicolas et al (2022) used a dynamic systems model approach to compare centralized and decentralized supply chain configurations and applied it to humanitarian supply chains to provide applicable inventory management strategies for food relief in relief operations [60].…”
Section: Review Of Humanitarian Supply Chain Assessment Methodsmentioning
confidence: 99%
“…Goal planning [55] The impact of supply chain agility (SCAG) and supply chain resilience (SCRES) on performance, mediated by organizational culture, was investigated DCV [56] Fuzzy MICMAC methodology was used to identify and analyze the factors that develop resilience in humanitarian supply chains Fuzzy-MICMAC [59] Interpretive structural modeling (ISM) was used to assess the barriers in the humanitarian supply chain in coastal Bangladesh under the influence of cyclones ISM [60] A dynamic systems model approach was used to compare centralized and decentralized supply chain configurations and apply them to humanitarian supply chains Dynamic systems model Thirteen representative indicators were selected to evaluate humanitarian supply chain resilience factors, and the VIKOR evaluation method was used to rank the resilience of humanitarian supply chains in five typical disaster areas…”
Section: Referencesmentioning
confidence: 99%